Injuries in children and adolescents with psychiatric disorders - Sara Agnafors; Jarl Torgerson; Marie Rusner; Anna Norman Kjellström (BMC, 2020)
Abstract Background Unintentional injuries are a leading cause of morbidity and mortality in children of all ages. Prevention strategies require knowledge of risk factors, and behavior and psychiatric disorders have been suggested to influence the risk of injury during childhood. While externalizing disorders have been found to increase the risk for injuries, results are mixed regarding internalizing disorders, such as affective and anxiety conditions, and Autism Spectrum Disorders (ASD). There is a need for large scale studies relying on robust data sources. The aim of the present study was to examine the association between psychiatric disorders and injuries requiring medical attention, in a large population-based cohort of 350,000 children and adolescents in Sweden. Methods Data were obtained from the regional health care database Vega. Psychiatric diagnoses and injury diagnoses obtained during 2014-2018 for individuals aged 0-17 years in 2016 were extracted. Descriptive statistics were used to examine differences in 5-year injury prevalence between children with and without different psychiatric diagnoses. Logistic regression was used in age-stratified models to test the association between psychiatric diagnoses and injuries requiring medical attention. Results The results show an increased risk for concurrent injuries in general, but the patterns vary by age and psychiatric disorder. Externalizing disorders and anxiety conditions were associated with concurrent injuries, while individuals with ASD had a lower risk for most injuries included. Affective disorders were associated with an increased risk for wounds, concussion, complications and poisoning, while the risk for fractures was decreased. Self-inflicted injury was more common in all psychiatric conditions investigated during adolescence, except for ASD. Children and adolescents with many types of psychiatric disorders were also at increased risk for a concurrent maltreatment diagnosis. Conclusions A general pattern of increased risk for concurrent injuries in children and adolescents with most psychiatric diagnoses was found, but the associations vary by age and type of psychiatric disorder. The results add to the literature on risk factors for injuries in children and adolescents, supporting diagnosis specific patterns. Several psychiatric diagnoses were associated with a marked increase in injury risk, indicating a high burden of disease for affected individuals.